Strangulated prolapsed ureterocele in an adult female - Delgado Pacheco, Manuel (2023)
Ureterocele is a cystic dilation of the distal ureter that exits into the urinary bladder. It is a rare condition in adults of which women are the most affected. Its clinical manifestations are very broad and among them the presence of a vulvar mass and symptoms of urinary obstruction stand out. We report the case of a strangulated ureterocele prolapse in a 54-year-old woman with a vulvar mass and signs of urinary obstruction. Initial management with reduction of the mass and finally decided to perform a ureteral reimplantation. Favorable evolution in medical follow-up.